Pathological Delta Oscillations in Hallucinogen Persisting Perception Disorder: A Case Report - Haslacher, David; Novkovic, Nikolina; Buthut, Maria; Heinz, Andreas; Soekadar, Surjo R. (Frontiers in Psychiatry, 2022)
Background: Hallucinogen persisting perception disorder (HPPD) is characterized by spontaneous recurrence of visual hallucinations or disturbances after previous consumption of hallucinogens, such as lysergic acid diethylamide (LSD). The underlying physiological mechanisms are unknown and there is no standardized treatment strategy available. Case presentation: A 33-year-old male patient presented with persistent visual distortions (halos around objects, intensified colors, positive after images and trails following moving objects) that developed after repeated use of hallucinogenic drugs at the age of 18. Symptoms developed gradually and worsened several months later, resulting in various pharmacological and psychosocial treatment attempts that remained unsuccessful, however. At presentation, 32-channel electroencephalography (EEG) showed increased delta activity over the occipital brain regions, reminiscent of occipital intermittent rhythmic delta activity (OIRDA) usually seen in children. Two sessions of cathodal (inhibitory) transcranial direct current stimulation (tDCS) over 30 minutes attenuated visual hallucinations and occipital delta activity by approximately 60%. The response persisted for over four weeks. Conclusions: Pathological delta activity over occipital brain regions may play an important role in the development and perpetuation of HPPD and can be attenuated by non-invasive brain stimulation.